A behavioral account of the labor market: the role of fairness concerns - Ernst Fehr; Lorenz Goette; Christian Zehnder (Institute for the Study of Labor (IZA), 2008)
In this paper, we argue that important labor market phenomena can be better understood if one takes (i) the inherent incompleteness and relational nature of most employment contracts and (ii) the existence of reference-dependent fairness concerns among a substantial share of the population into account. Theory shows and experiments confirm, that even if fairness concerns were only to exert weak effects in one-shot interactions, repeated interactions greatly magnify the relevance of such concerns on economic outcomes. We also review evidence from laboratory and field experiments examining the role of wages and fairness on effort, derive predictions from our approach for entry-level wages and incumbent workers' wages, confront these predictions with the evidence, and show that reference-dependent fairness concerns may have important consequences for the effects of economic policies such as minimum wage laws.
urn:nbn:de:101:1-2009010789
Keywords: C7; D00; D2; D8; J2; L2; 330; Fairness; contracts; wages; effort; experiments; Arbeitsmarkt; Verhaltensökonomik; Gerechtigkeit; Arbeitsvertrag; Lohn; Leistungsmotivation; Test; Interner Arbeitsmarkt; Mindestlohn